Human rights are not for sale - Razak, Dzulkifli Abd (2011)
WHILE trouble is brewing in the Middle East and the Arab world, Europe and the West in general, are also facing their own tensions. In mid-February, for example, the Council of Europe openly backed its increasing number of members who denounced "multiculturalism" as a failure, and dubbed it a potential threat to the security of the region.